Relation of Macromolecular Synthesis in Streptococci to Efficiency of Transformation by Markers of Homospecific and Heterospecific Origin - Deddish, Peter A. (1974)
In previous studies with Streptococcus sanguis and S. pneumoniae as recipients and donors of transforming deoxyribonucleic acid (DNA), it was found that heating recipients just prior to exposure to DNA caused an increase in the number of transformants induced by heterospecific DNA relative to that induced by homospecific DNA. In the present studies, S. sanguis recipients were found to recover from this effect of heat (48 C, 15 min) when incubated at 37 C before exposure to DNA. Inhibitors of nucleic acid synthesis, such as rifampin, 5-fluorodeoxyuridine, actinomycin, and p-hydroxyphenylazo-uracil, but not inhibitors of protein synthesis, such as chloramphenicol and erythromycin, prevented recovery from the effect of heat. Inhibitors of nucleic acid synthesis caused changes in unheated cells similar to those observed with heat treatment; these changes included increased transformability by genetically hybrid DNA and by low-efficiency markers in homospecific DNA. The effect of a combination of heat and inhibitors on transformation by heterospecific DNA was greater than when single treatments were used. The most effective inhibitor used alone was rifampin: in treated recipient cells, the yield of transformants produced by a given amount of irreversibly bound heterospecific DNA was increased without a significant change in the yield of transformants produced by bound homospecific DNA. A cell being doubly transformed by homospecific and heterospecific DNA was enhanced specifically in its transformability with the latter as a consequence of rifampin treatment. Treatment with rifampin also increased co-transformation by linked heterospecific markers. The period during which recipient cells were sensitive to the effects induced by rifampin and fluorodeoxyuridine lasted from 10 to 20 min after DNA uptake.